2020
DOI: 10.1002/zaac.202000234
|View full text |Cite
|
Sign up to set email alerts
|

MoP@C Supported on Absorbent Cotton as a Highly Efficient Catalyst towards Hydrodechlorination Reaction

Abstract: This paper reports a method for preparing MoP@C synthesized from absorbent cotton. While the influence of the amount of absorbent cotton on its composition and morphology are also explored. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) confirmed that MoP@C and unmodified MoP exhibit completely different microscopic morphologies. With the gradual increase in the quality of absorbent cotton, the morphology of catalysts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…In addition, carbon can accelerate the electron conductivity of catalysts, thereby enhancing the catalytic performance in different reaction [22–24] . For example, our group previously reported that the modification of MoP with absorbent cotton derived carbon material confirmed that the appropriate carbon matrix was conducive to increasing the specific surface area of MoP@C catalyst to improve the hydrogenation activity [25] . However, the thermal stability of MoP modified by the single carbon material is poor, while oxygen element has recently been reported to occupy an important position in the catalytic process of HDC, often playing a role in improving the stability of MoP cycle and active sites [26–28] .…”
Section: Introductionmentioning
confidence: 94%
“…In addition, carbon can accelerate the electron conductivity of catalysts, thereby enhancing the catalytic performance in different reaction [22–24] . For example, our group previously reported that the modification of MoP with absorbent cotton derived carbon material confirmed that the appropriate carbon matrix was conducive to increasing the specific surface area of MoP@C catalyst to improve the hydrogenation activity [25] . However, the thermal stability of MoP modified by the single carbon material is poor, while oxygen element has recently been reported to occupy an important position in the catalytic process of HDC, often playing a role in improving the stability of MoP cycle and active sites [26–28] .…”
Section: Introductionmentioning
confidence: 94%